Nation in imagination : essays on nationalism, sub-nationalisms, and narration - Association for Commonwealth Language and Literature Studies. Conference 2004 : Hyderabad, India); Vijayasree, C.; Association for Commonwealth Language and Literature Studies (Hyderabad : Orient Longman, 2007)
Transcript of papers presented at the 13th Triennial Conference of the Association for Commonwealth Language and Literature Studies held in August 2004 in Hyderabad India.
Machine derived contents note: Introduction / C. Vijayasree -- Section 1: Re-imagining the Nation -- Nationalism and the Imagination / Gayatri Chakravorty Spivak -- Re-imagining Communities / Helen Tiffln -- Nationalism and Peculiarities of the Indian / Aijaz Ahmad -- Varieties of Nationalism: Culture and Resistance in the Indian English Novel / Satish C. Aikant -- Benedict Anderson Revisited / TimJ. Cribb -- British Orientalism and the Hindu Nation: Robert Southey's Palimpsest of Kehama, 1800-1810 / Daniel Sanjiv Roberts -- Nation, Literature and Institutional Change / Leslie Monkman -- A Roadmap to Civilianisation / Probal Dasgupta -- The Emperor's New Clothes / Bill Ashcroft -- Section 2: De-centring the Nation -- The Caledonian Diaspora in Australia: A Foot in Each Camp / Susan Cowan -- From Empire to Empire?: Writing the Transnational Anglo-Indian Self in Australia / Debjani Ganguly -- Gendering ImagiNations: Stories by Some Canadian 'Mothers of the Nation' / Wendy Robbins -- Ghost Spaces, Living Histories: Memory and Photography in Contemporary Native North American Women's Poetry / JenniferAndrews -- Woman and Nation in the Works of Contemporary Female Egyptian Writers / Stella Borg Barthet -- Fabricating Community: Local, National and Global in Three Indian Novels / Paul Sharrad -- Subversive Migrant Labour in Monica Ali's Brick Lane and Zadie Smith's White Teeth / Devon Campbell-Hall -- The Nation and the Indian Tribes: A Diachronic View / Ivy Imogene Hansdak.
Includes bibliographical references and index.
Keywords: Literature, Modern -- 20th century -- History and criticism; Indic literature -- 20th century -- History and criticism -- Congresses; Postcolonialism in literature -- Congresses; Postcolonialism -- India -- Congresses; Nationalism -- India